ANTIOXIDANT THERAPEUTIC ACTIONS OF MEDICINAL PHYTOCHEMICALS, SILYMARIN AND SILIBININ, ON STREPTOZOTOCIN DIABETIC RATS: FIRST NOVEL COMPARATIVE ASSESSMENT OF STRUCTURAL RECOVERIES OF HISTOLOGICAL AND ULTRASTRUCTURAL CHANGES ON ISLETS OF LANGERHANS, Î’-CELLS, MITOCHONDRIA AND NUCLEUS - El-far, Mohamed; Negm, Amr; El-azim, Amira Abd; Wahdan, Mona (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: We studied correlation between antioxidant properties of Silymarin and Silibinin and the restoration and recovery of normal structure of islets of Langerhans Î²-cells and mitochondria in Streptozotocin-diabetic rats. Methods: Rats rendered diabetic and one week after diabetes induction, rats received orally Silymarin or Silibinin (100 mg/Kg). Biochemical parameters: glucose, HbA1c, lipid profile, hepatic SOD, GSH and MDA were determined. Furthermore, changes in islets of Langerhans, Î²-cells as well as mitochondria were recorded using electron microscope. Results: 1) Silymarin and Silibinin treatment(s) of STZ-diabetic rats can correct and reverse the imbalance between ROS and antioxidant defense by restoring and augmentation of its capacity by significantly increasing SOD, GSH and modulating lipid peroxidation (by significantly decreasing MDA). 2) We provided evidence, using EM technique, to prove that hypoglycemic/antidiabetic/therapeutic actions of both Silymarin and Silibinin (by improving significantly both glucose and insulin levels), may be due to their ability to stimulate Î²-cells to secrete insulin through restoring antioxidant endogenous properties and hence, recovery of intact insulin secretory granules as well as restoration of normal structure of pancreatic endocrine cell islets of Langerhans. 3) We provided first novel comparative assessment of histological and ultrastructural changes on islets of Langerhans and Î²-cells as well as complete mitochondrial recovery by oral Silymarin and Silibinin treatment (s) in diabetic rats. Conclusion: Both agents show Hypoglycemic, hpolipidemic and antioxidant properties, exhibit structural recovery of mitochondria, intact insulin secreting granules and nucleus, they act as anti-mitochondrial loss and/or dysfunction in diabetes. Keywords: Silymarin, Silibinin, Diabetes, Antidiabetic agents, Antioxidants, Electron Microscope, Mitochondrial and Î²-cells Recovery